The Energy Level Conundrum of Organic Semiconductors in Solar Cells (Adv. Mater. 35/2022). Issue 35 (1st September 2022) - Bertrandie, Jules; Han, Jianhua; De Castro, Catherine S. P.; Yengel, Emre; Gorenflot, Julien; Anthopoulos, Thomas; Laquai, Frederic; Sharma, Anirudh; Baran, Derya
Abstract : Organic Semiconductors In article number 2202575, Anirudh Sharma, Derya Baran, and co‐workers unravel the inconsistencies of the determination of the absolute energy levels in organic semiconductors and their implication, particularly in the field of organic solar cells. In the cover image, the charges generated by the excitation of the materials by light are represented by the energy balls with feet and hands: electrons are represented in green and holes in red. The charges are jumping down a staircase, representing the energy levels of different organic semiconductor materials.